2014
DOI: 10.1016/j.jmb.2014.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Remodeling of Rad51–DNA Complexes by Srs2 Is Mediated by a Specific Protein–Protein Interaction

Abstract: The yeast Srs2 helicase removes Rad51 nucleoprotein filaments from single-stranded DNA (ssDNA), preventing DNA strand invasion and exchange by homologous recombination. This activity requires a physical interaction between Srs2 and Rad51, which stimulates ATP turnover in the Rad51 nucleoprotein filament and causes dissociation of Rad51 from ssDNA. Srs2 also possesses a DNA unwinding activity and here we show that assembly of more than one Srs2 molecule on the 3' ssDNA overhang is required to initiate DNA unwin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Furthermore, the immobilized protein assay demonstrates that not Srs2, but a monomer of Sgs1 is sufficient for unwinding the DNA duplex. This is consistent with the previous finding that multimers of Srs2 are required for efficient unwinding (Qiu et al, 2013), with an unwinding concentration threshold (50nM), below which unwinding is limited (Lytle et al, 2014). …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, the immobilized protein assay demonstrates that not Srs2, but a monomer of Sgs1 is sufficient for unwinding the DNA duplex. This is consistent with the previous finding that multimers of Srs2 are required for efficient unwinding (Qiu et al, 2013), with an unwinding concentration threshold (50nM), below which unwinding is limited (Lytle et al, 2014). …”
Section: Discussionsupporting
confidence: 93%
“…Here, we employed the full-length Srs2 protein instead of the C-terminal deletion mutant, Srs2 CΔ276 used in our previous study, although both have been shown to have similar helicase activities (Qiu et al, 2013). The concentration of Srs2 used here is comparable to previous studies (Anand et al, 2012; Bhattacharyya and Lahue, 2004) where we do not anticipate significant unwinding of the dsDNA (Lytle et al, 2014). When Srs2 (10nM) and ATP (1mM) was added to the pdT20 substrate, we observed a rapid FRET fluctuation between two FRET states (Figure 1B), consistent with the previously reported repetitive movement of Srs2 on single strand (ss) DNA, fueled by ATP hydrolysis (Qiu et al, 2013).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…In addition, recent studies have shown that E. coli UvrD translocates either as a monomer or as two tandem monomers, and that the tandem monomers are more processive than a single monomer (Comstock et al, 2015; Lee et al, 2013). Similarly, recent biochemical results have suggested that more than one Srs2 monomer is required for efficient DNA unwinding (Lytle et al, 2014). Our work now demonstrates that processive disruption of Rad51 filaments involves multiple Srs2 molecules acting upon the same filament end.…”
Section: Discussionmentioning
confidence: 79%